The effect of training experience on postural control in competitive wrestlers - Rzepko, M.; Drozd, S.; Zeglen, P.; Krol, P.; Bajorek, W.; Czarny, W. (Journal of Human Kinetics, 2019)
The aim of this study was to evaluate the effects of training experience in wrestling on postural control. Fourteen elite athletes with at least 8 years of wrestling training and competition experience participated in the study. The control group consisted of fifteen healthy adults who were not competitive athletes. The center of pressure (COP) trajectories were recorded with the use of an AMTI force plate at a sampling frequency of 50 Hz. The rambling-trembling decomposition method was used to analyze the COP trajectory data. The main finding was a significant effect of training experience on postural control in only the sagittal plane. Interestingly, significant differences in velocity were observed for the trembling component of the COP. All described variables were significantly higher in wrestlers. We hypothesized that balance training may lead to task-specific neural adaptations at the spinal and supraspinal levels. It was concluded that further research of high methodological quality is needed to determine the effect of training experience on balance control in elite athletes. Additionally, this effect should be observed in youth athletes, as it may be treated as a selection criteria in the training process.